Pengaruh Kompensasi Motivasi terhadap Kinerja Karyawan pada Koperasi Pegawai Negeri Bina Kesan Bojonggede - Wulan Syakirah; Ratnawaty Marginingsih; Wiwit Rohaeni Yulianti (Jurnal Manajemen Bisnis Era Digital, 2025)
Bina Kesan Cooperative in Bojonggede is a cooperative whose main activities focus on assisting members in meeting financial needs, improving welfare, and encouraging the development of members’ businesses. This study aims to determine the extent to which compensation and motivation influence employee performance. The research method employed was quantitative with a descriptive approach, while the sampling technique was determined using the Slovin formula to ensure that the number of respondents was representative. Data were collected through questionnaires that had been tested for validity and reliability, and then processed using SPSS version 27. The statistical test results indicate that the t-value of 1.492 is greater than the t-table value of 0.2681, with a significance level of 0.00 < 0.05, leading to the rejection of the null hypothesis (H₀). All R-values of 0.05 > R-table 3.18 demonstrate that the research instruments were valid. Furthermore, the F-value of 180.803 is higher than the F-table value of 2.00758, with a significance level of 0.00 < 0.05, confirming that the regression model is significant. Based on these findings, it can be concluded that compensation and motivation variables simultaneously have a positive and significant effect on employee performance at Bina Kesan Cooperative, Bojonggede.